Organic Management of Vegetable Diseases Part I: Soilborne Pathogens - Gary Vallad; Amanda Gevens (EDIS, 2008)
PP-253, a 5-page fact sheet by Gary Vallad and Amanda Gevens, is an overview of six “REPEAT” principles of plant-disease control (Resistance, Eradication, Protection, Exclusion, Avoidance, and Therapy) with an emphasis on methods acceptable in certified organic vegetable production for controlling plant disease caused by soilborne pathogens. Published by the UF Department of Plant Pathology, June 2008.